Malaria and leishmaniasis: Updates on co-infection - Ornellas-Garcia, Uyla; Cuervo, Patricia; Ribeiro-Gomes, Flávia Lima (Frontiers in Immunology, 2023)
Malaria and leishmaniasis are endemic parasitic diseases in tropical and subtropical countries. Although the overlap of these diseases in the same host is frequently described, co-infection remains a neglected issue in the medical and scientific community. The complex relationship of concomitant infections with Plasmodium spp. and Leishmania spp. is highlighted in studies of natural and experimental co-infections, showing how this “dual” infection can exacerbate or suppress an effective immune response to these protozoa. Thus, a Plasmodium infection preceding or following Leishmania infection can impact the clinical course, accurate diagnosis, and management of leishmaniasis, and vice versa. The concept that in nature we are affected by concomitant infections reinforces the need to address the theme and ensure its due importance. In this review we explore and describe the studies available in the literature on Plasmodium spp. Leishmania spp. co-infection, the scenarios, and the factors that may influence the course of these diseases.